Treatment of liquid pharmaceutical industry effluents by Fenton's processes| - Oliveira, Ana Carolina Lopes (2013)
Dissertação de mestrado em Química Farmacêutica Industrial,, apresentada à Faculdade de Farmácia da Universidade de Coimbra.